PENYULUHAN PEMANFAATAN OBAT TRADISONAL UNTUK DEMAM, BATUK, PILEK PADA ANAK DI WILAYAH BINTARA BEKASI BARAT (Jurnal Mitra Masyarakat (JMM), 2023)
There was a withdrawal of syrup medicinal products used as fever, cough, and cold medicines due to the discovery of impurities that exceeded the safe threshold. People finally switched to using traditional medicine to treat fever,coughs, and colds in children. The aim of the activity is to provide information about medicinal plants that can be used to treat fever, coughs and colds in children as well as how to make traditional medicines in the form of herbal medicine. This service activity begins with searching for literature and outreach targets, preparation materials, implementation of outreach, and evaluation. There was an increase in the post-test, namely 64% of participants had good knowledge and 36% of participants had very good knowledge. Providing information in the context of socializing the use of traditional medicine can increase knowledge of participants, mothers who have children under five in the PKK RW 14 Bintara area.